Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/ismej.2017.197
|View full text |Cite
|
Sign up to set email alerts
|

Microbial life on a sand grain: from bulk sediment to single grains

Abstract: Globally, marine surface sediments constitute a habitat for estimated 1.7 × 1028 prokaryotes. For benthic microbial community analysis, usually, several grams of sediment are processed. In this study, we made the step from bulk sediments to single sand grains to address the microbial community directly in its micro-habitat: the individual bacterial diversity on 17 sand grains was analyzed by 16S ribosomal RNA gene sequencing and visualized on sand grains using catalyzed reporter deposition fluorescence in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 54 publications
5
84
0
Order By: Relevance
“…Compared to glass beads, sand grains are more textured and denser, allowing enhanced microbial attachment. Furthermore, sand grains enhances the growth of microorganisms, it has been found that each sand grain can habit 10 5 cells (Probandt et al, 2018) with only 0.5 µm between each cell (Probandt et al, 2018). Sand grains can shield microorganism from mechanical sheer stress, while providing necessary porosity for substrate availability (Probandt et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to glass beads, sand grains are more textured and denser, allowing enhanced microbial attachment. Furthermore, sand grains enhances the growth of microorganisms, it has been found that each sand grain can habit 10 5 cells (Probandt et al, 2018) with only 0.5 µm between each cell (Probandt et al, 2018). Sand grains can shield microorganism from mechanical sheer stress, while providing necessary porosity for substrate availability (Probandt et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Streptomycetes in soil live on soil grains where overall cell densities are anticipated to be heterogenous and patchy (Probandt et al, 2018). One of the challenges to understanding the role of antibiotics in nature is that their estimated concentrations in bulk soil are extremely small.…”
Section: Discussionmentioning
confidence: 99%
“…Microscopic analysis of sand grains from marine sediments revealed that colonization is highly uneven, with protected areas on individual grains being more densely populated than exposed areas (Probandt et al, 2018). Because the fitness of S. griseus scales with density, the colonization density in nature will undoubtedly influence the benefits of antibiotic production.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, their cellular metabolic rates are lower than the required metabolic level (10 4 -10 5 protons per second) for the rotation of a single bacterial flagellum in E. coli 17 , suggesting that these anammox bacteria do not have enough metabolic activity to fuel the flagellar rotation. Instead, we speculate the function of the flagella of anammox bacteria in the subsurface are more likely facilitating their adhesion onto particle surfaces 18 , as the majority of microbial cells in marine sediments are particle-attached 19 . This could provide them a protection in unfavorable conditions like the oxic zone where they could hide in anoxic microniches.…”
Section: Main Textmentioning
confidence: 93%